Compromised concentrations of ascorbate in fluid lining the respiratory tract in human subjects after exposure to ozone. Issue 7 (1st July 1999) - Mudway, I S; Krishna, M T; Frew, A J; MacLeod, D; Sandstrom, T; Holgate, S T; Kelly, F J
Abstract : OBJECTIVES: Ozone (O3) imposes an oxidative burden on the lung in two ways. Firstly, directly as a consequence of its oxidising character during exposure, and secondly, indirectly by engendering inflammation. In this study the second pathway was considered by ascertaining the impact of O3 on the redox state of the fluid lining the respiratory tract 6 hours after challenge. METHODS: Nine subjects were exposed in a double blind crossover control trial to air and 200 ppb O3 for 2 hours with an intermittent exercise and rest protocol. Blood samples were obtained and lung function (forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1)) assessed before, immediately after, and 6 hours after exposure. Bronchoalveolar lavage (BAL) was performed 6 hours after challenge. Inflammation was assessed in BAL fluid (total and differential cell counts, plus myeloperoxidase concentrations), and plasma and BAL fluid redox state were determined by measuring concentrations of antioxidants and markers of oxidative damage. RESULTS: Neutrophil numbers in BAL fluid increased 2.2-fold (p = 0.07) 6 hours after exposure and this was accompanied by increased myeloperoxidase concentrations in BAL fluid (p = 0.08). On the other hand, BAL fluid macrophage and lymphocyte numbers decreased 2.5-fold (p = 0.08) and 3.1-fold (p = 0.08), respectively at this time. Of the antioxidants examined, only ascorbate in BAL fluid was affected by O3, falling in all subjects relative to air values (0.1 (0.0-0.3) v 0.3 (0.2-1.2) mumol/l (p = 0.008)). A marginal decrease in plasma ascorbate was also detected at this time (p < 0.05). Although the decrease in macrophage numbers seemed to be causally related to the increase in neutrophils (R = -0.79), myeloperoxidase concentrations (R = -0.93) and ascorbate concentrations (R = 0.6), no clear associations were apparent between ascorbate changes and neutrophils or myeloperoxidase concentration after O3. CONCLUSIONS: Ascorbate in the fluid lining the respiratory tract is depleted as a consequence of O3 exposure at 6 hours after exposure. This was contemporaneous with, although not quantitatively related to the increase in neutrophil numbers and myeloperoxidase concentrations. Decreased macrophage numbers 6 hours after O3 related to the degree of neutrophilic inflammation with populations conserved where ascorbate concentration in the fluid lining the respiratory tract were high after exposure. These results imply that ascorbate has a critical protective role against inflammatory oxidative stress induced by O3.